A new way of achieving multi-path routing in wireless networks. (28th January 2020) - Temar, Abdeldjalil; Geuzouri, Mustapha; Mbarek, Nader
In the 21st century, the wireless technology is still developing rapidly and trying to be 'Faster, Higher, and Stronger': faster data rate, higher bandwidth and stronger connectivity. Wireless Mesh Networks (WMN) have been envisioned as an important solution to the next generation wireless networking which can be used in wireless community networks, wireless enterprise networks, transportation systems, home networking and last-mile wireless internet access. They also provide a cheap, quick and effective way for building wireless data networks. Considering the nature of these networks, routing is a key process for operating the WMN. This paper proposes a new way of creating multi-path routing protocols based on a fusion between multicast and unicast routing protocols to get different routes (node-disjoint or link-disjoint) from the source to its destination. The simulation results using Network Simulator 2 (NS-2) show that our new Multi-path Routing Protocol (Fusion) outperforms Ad hoc On-Demand Distance Vector (AODV) and Ad hoc On-demand Multi-path Distance Vector (AOMDV) routing protocols in terms of average network throughput, end-to-end delay, and number of flows.